Quality indicators in pituitary surgery: a need for reliable and valid assessments. What should be measured?. (9th February 2016) - Powell, Michael; Grossman, Ashley
Summary: Engagement with improving the quality of clinical care is a key component of medical professionalism. Central to Quality Improvement (QI) agenda are the development of valid, reliable and accurate quality metrics. We cannot improve what we do not measure. Pituitary surgery, which in the 21st century usually means trans‐sphenoidal surgery (TSS), is unusual; it is a neurosurgical procedure in which complex outcomes can be measured precisely. We have clear guidelines for establishing remission/cure in functional endocrine disease and precise diagnostic tools with which to investigate our patients. Visual recovery can be equally precisely measured with standardised equipment. Moreover, TSS is one of the commonest major surgical procedures carried out in the 34 UK individual neurosurgical units. Most will carry out about 30–40 procedures each year, with four or five units notably higher with numbers in excess of one hundred cases. There are, potentially, plenty of data out there. Given this background, how best should we measure quality in this important area of clinical practice?